Awareness advertising influence on consumers buying intention: Exploring attitude as a mediating factor - Alqaysi S.J.; Zahari A.R.; Khudari M. (EnPress Publisher, LLC, 2025)
This study investigates the intricate relationship between awareness advertising and buying intention among Iraqi grocery shoppers, exploring the mediating role of consumer attitude. Employing a quantitative approach, the authors surveyed 300 shoppers. Using a random sampling technique. To ensure rigor and validity, the authors rigorously analyzed the relationships using partial least squares structural equation modelling (PLS-SEM) based on 288 valid responses. The findings reveal that awareness advertising significantly impacts buying intention, mediated by consumer attitude. These insights offer valuable management implications for product marketers. Sufficient brand awareness attracts consumer attention, shapes positive attitudes, and ultimately drives purchase decisions. This study further validates the theoretical model of consumer response by empirically establishing consumer attitude as a central intermediary between awareness advertising and buying intention within the Iraqi market context. ? 2024 by author(s).